Identifying Euglena Gracilis Metabolic and Transcriptomic Adaptations in Response to Mercury Stress - Mangal, Vaughn; Donaldson, Michael E.; Lewis, Ainsely; Saville, Barry J.; Guéguen, Céline (Frontiers in Environmental Science, 2022)
Mercury contamination in aquatic systems poses a serious environmental stress to phototrophic plankton. We used Euglena gracilis to gain an understanding of the physiochemical changes resulting from mercury stress across the transcriptome and metabolome. Using a combination of Fourier Transform Ion Cyclotron Resonance Mass Spectrometry (FT-ICR-MS) and RNA-sequencing, we identified metabolomic and transcriptomic changes both within and outside cellular space after mercury exposure. Metabolic profiles of E. gracilis were less diverse after mercury exposure, highlighting an overall refinement of metabolites produced. Significant fold changes in cysteine, glutathione, and amino acid-based metabolites were found (p < 0.05) within the mercury exposed cells and in extracellular space than in untreated cultures. Using integrated omics analyses, a significant upregulation of transcripts and metabolites involved in amino acid synthesis, cellular responses to chemical stress, reactive oxygen species detoxification, and electron transport were identified. Together the enrichment of these pathways highlights mechanisms that E. gracilis harness to mitigate oxidative stress at sublethal concentrations of mercury exposure and give rise to new biomarkers of environmental stress in the widely distributed E. gracilis.